The timing of 40% oral dextrose gel administration after birth does not influence the incidence of hypoglycemia in at-risk infants - De Bernardo Giuseppe; Giordano Maurizio; Langella Carmen; Piccirillo Daiana; Giada Zollo; Sordino Desiree; Morlino Francesca; Beretta Virginia; Perrone Serafina (Elsevier, 2024)
Background: Hypoglycemia is the most common metabolic disorder seen in newborns and can cause long-term neurological damage, developmental disorders and poor later school performance. In recent years, the use of oral dextrose gel is widely used as a first-line treatment for prevention of asymptomatic neonatal hypoglycemia. Primary aim of our study was to evaluate the effects of oral administration of 40 % dextrose gel at 30 or 60 min of life on the incidence of hypoglycemia in at-risk infants born by vaginal or cesarean delivery in the first 48 h of life. Secondary aim was to evaluate if the oral administration of 40 % dextrose gel can decrease the use of formula milk. Methods: A retrospective observational study was conducted at the Buon Consiglio Fatebenefratelli Hospital. Newborns birth by vaginal or Caesarean section and that assumed 40 % dextrose gel at 30 or 60 min after birth were respectively divided in 4 groups (Group A, Group B, Group C and Group D). Glycemic monitoring was then carried out with serial measurements at 2, 4, 6, 12 and 48 h of life. Results: No statistically significant differences were found in the reduction of the incidence of hypoglycemia with respect to the timing of administration of the dextrose gel (χ2(3)=0,450; p = 0,930). The use of formula milk was higher in newborns born by Caesarean section that assumed dextrose gel at 30 min of life than other groups (χ2(3)=11,616; p = 0,009; OR (95 %CI)= 3,033 (1,286-7,153). Conclusions: The use of 40 % oral dextrose gel is a useful strategy for the prevention of hypoglycemia especially in infants at risk, independently to mode of delivery. Timing of administration of dextrose gel did not have effect on the incidence of hypoglycemia among groups. Newborns born by Caesarean section and that assumed 40 % oral dextrose gel at 30 min of life assume more formula milk compared to other groups.